Estudios en frijol ejotero en Guatemala - Ajquejay A., S. (International Center for Tropical Agriculture, 1987)
Since 1982, the behavior of snap bean cv. of determinate growth from North American commercial houses is being evaluated in Guatemala. Charts wiht data on yield and av. production (t/ha) and the agronomic characteristics of the evaluated cv. are included. Line 124C outstood for yield and low fiber content, characteristics that favor its acceptance in the area. (CIAT)